Double Knockdown of PHD1 and Keap1 Attenuated Hypoxia-Induced Injuries in Hepatocytes - Liu, Jing; Li, Yiping; Liu, Lei; Wang, Zhi; Shi, Chuanbing; Cheng, Zhengyuan; Zhang, Xiaoyi; Ding, Fengan; Chen, Ping Sheng (Frontiers in Physiology, 2017)
Background and Aims: Hypoxia and oxidative stress contribute towards liver fibrosis. In this experiment, we used small hairpin RNA (shRNA) to interfere with the intracellular oxygen sensor—prolyl hydroxylase 1 (PHD1) and the intracellular oxidative stress sensor—kelch-like ECH associated protein 1 (Keap1) in the hypoxic hepatocytes in order to investigate the function of PHD1and Keap1. Methods: We first established the CCl4-induced liver fibrosis model, subsequently, the level of the PHD1, hypoxia-inducible factor-1α (HIF-1), hypoxia-inducible factor-2α (HIF-2), Keap1, and nuclear factor-erythroid 2 p45-related factor 2 (Nrf2) were detected in liver tissues. Simultaneously, AML12 cells co-transfected with PHD1 and Keap1shRNAs were constructed in vitro, then the intracellular oxidative stress, the proportion of cells undergoing apoptosis, and cell viability were measured. The expression of pro-fibrogenic molecules were analyzed via quantitative real-time polymerase chain reaction (qRT-PCR) and western blot. The level of alpha-1 type I collagen (COL1A1) was determined using an enzyme-linked immunosorbent assay (ELISA). Finally, serum-free ‘conditioned medium’ (CM) from the supernatant of hypoxic AML12 hepatocytes was used to culture rat hepatic stellate cells (HSC-T6), and the levels of fibrosis-related molecules, apoptosis, and cell proliferation were determined. Results: The marker of hypoxia—HIF-1 and HIF-2 in the livers with fibrosis were upregulated, however, the increase in PHD1 expression was not statistically significant in comparison to the control group. Signs of oxidative stress—Keap1 was increased, while the expression of Nrf2 , one of the Keap1 main downstream molecules, was reduced in the hepatocytes. And in vitro, the double-knockdown of PHD1 and Keap1 in AML12 hepatocytes presented with decreased hypoxia-induced oxidative stress and apoptosis, furthermore, these hypoxic AML12 cells showed the increased cell viability and the doweregulated expression of pro-fibrogenic molecules. In addition, HSC-T6 cells cultured in the hypoxic double-knockdown CM demonstrated the downregulation of fibrosis-related molecules, diminished cell proliferation, and enhanced apoptosis. Conclusions: Our study demonstrated that double-knockdown of PHD1 and Keap1 attenuated hypoxia and oxidative stress induced injury in the hepatocytes, and subsequently inhibited HSC activation, which offers a novel therapeutic strategy in the prophylaxis and treatment of liver fibrosis.